The best American science & nature writing 2025 - Orlean, Susan; Green, Jaime (Best American series., 2025)
"The best science and nature writing-which these stories represent-reminds us of the wide world and our connection to it, and the multitude of ways we make our place in it," writes Susan Orlean in her introduction. This year's collection masterfully guides us through exotic locations and groundbreaking research, leading us to consider complex and utterly fascinating questions about the world. How does it feel to camp in one of the hottest places on Earth? Is the ability to recognize and remember faces a sign of intelligence? What does it mean for a species to be wild or invasive-are city pigeons and rats less deserving than the coyotes that recently wandered down from Westchester? Encompassing the strangeness and, at times, severity of our world, these stories are urgent, vital, and ultimately inspiring. As Orlean eloquently observes, "Science keeps unlocking mysteries, revealing secrets, helping us heal. And as imperiled as nature seems, it remains amply, gloriously gorgeous: The world is still full of beauty."